2015
DOI: 10.1116/1.4929883
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of small microfluidic valves for studies of mechanical properties of bacteria

Abstract: Lab-on-a-chip platforms present many new opportunities to study bacterial cells and cellular assemblies. Here, a new platform is described that allows application of uniaxial stress to individual bacterial cells while observing the cell and its subcellular assemblies using a high resolution optical microscope. The microfluidic chip consists of arrays of miniature pressure actuated valves. By placing a bacterium under one of such valves and partially closing the valve by externally applied pressure, the cell ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…1d ) instead of syringe pumps to allow for easy streamlining and fast response times. Although MACS essentially exploits valve actuation to immobilize cells between a glass coverslip and a PDMS membrane similar to what was described earlier 23 24 , simply collapsing the valve (that is, going directly from open to closed state) yields extremely poor trapping efficiency due to the rapid displacement of liquid. Instead, MACS relies on three distinct valve states, achieved by controlling both the pressure of the valve ( P valve ) and the pressure driving the flow ( P flow ) of the cell suspension.…”
Section: Resultsmentioning
confidence: 99%
“…1d ) instead of syringe pumps to allow for easy streamlining and fast response times. Although MACS essentially exploits valve actuation to immobilize cells between a glass coverslip and a PDMS membrane similar to what was described earlier 23 24 , simply collapsing the valve (that is, going directly from open to closed state) yields extremely poor trapping efficiency due to the rapid displacement of liquid. Instead, MACS relies on three distinct valve states, achieved by controlling both the pressure of the valve ( P valve ) and the pressure driving the flow ( P flow ) of the cell suspension.…”
Section: Resultsmentioning
confidence: 99%
“…In deformed regions of the channel, the cells grow in multiple rows or were tilted relative to the direction of the channel. Based on our earlier studies (Yang et al, 2015 ), stress analysis of such channels has shown that pressures in the 0.2 MPa range are needed to widen channels at their midplane by few hundred nanometers. Similar or even larger pressures must have been present in the broadened regions of the channel.…”
Section: Resultsmentioning
confidence: 99%
“…The channels in PDMS elastomers are created using 4″ silicon (Si) wafer molds. The fabrication of the Si molds follows the process described earlier (Yang et al, 2015 ). Briefly, the patterns of dead-end channels are defined by e-beam lithography using a JEOL JBX-9300FS electron beam lithography system (JEOL, Japan) with ZEP520A, a positive tone e-beam resist (ZEON Chemical, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation